Building and codifying the scale of intolerance among university students in Baghdad - Ali Abbas, Warda; Razzaq Kadhum, Sahira; Abdul-Hussein Neamah, Iqbal (International Journal of Psychosocial Rehabilitation, 2020)
Intolerance is the result of psychological processes of the individual's perception of the concept of belonging and his awareness of the existence of external groups that may destabilize its security and stability or distinguish it from other groups by what is known as social classification, and intolerance is also a product of cognitive processes of a general nature that lead to the simplification of the surrounding social world to make it more amenable to dealing with it and answers many Among the questions that he had about the nature of social relations between individuals. Among these theories adopted by the researchers is the theory of social learning of Benadura and Waltz, which indicates that fanaticism is possible for an individual to learn as a result of imitation, simulation, and guidance to others close to him, especially parents in the early stages.1 It revolves around situations within other groups in society (2001-23), which generates the emergence of intolerant trends, whether in beliefs or apparent behaviour. In our time, the media is the most influential source for learning and spreading fanatic trends that are led by parties and sects that serve external and internal groups with specific goals and interests (2008-4-4).This phenomenon is frequently found in societies that have undergone certain wars or conflicts, which makes encouraging this phenomenon. A necessity to stay. From here came the importance and problem of research in studying this phenomenon among an important segment of society, namely university students, on whom the progress or delay of any modest contribution state by researchers to stand up when studying the phenomenon of intolerance and help those in the educational process to prevent the spread of the phenomenon of intolerance.